Review on Melanin from Marine Actinomycetes - Vasanthabharathi; S. Jayalakshmi (Journal of Basic & Applied Sciences, 2020)
Marine microorganisms have become an important source of pharmacologically active metabolites. It is an important part of the natural products which includes secondary metabolites, antimicrobial, antitumor, anitoxidant and antiviral compounds. For the past few decades, marine organisms have been the focus of a worldwide effort for the discovery of novel natural products. Actinomycetes from the marine environment one of the novel bioactive producer. The brown-black pigment has been referred to as 'melanin ' and as ' melanin like' pigment. It has been shown to protect micro-organisms against U-V radiation, enzymatic lysis, oxidants and killing by alveolar macrophages. Melanin has an immense biotechnological application, but understanding the importance and novelty of melanin from marine actinomycete is very little. At this juncture, this review briefly describing the importance melanin from marine actinomycetes.